Correlation between Hyperalgesia and Upregulation of TNF-α and IL-1β in Aqueous Humor and Blood in Second Eye Phacoemulsification: Clinical and Experimental Investigation. (26th August 2021) - Yang, Ruibo; Liu, Chang; Yu, Di; Ma, Lechong; Zhang, Yan; Zhao, Shaozhen
Abstract : The aim of this study was to explore the correlation between intraoperative hyperalgesia of the second eye and the dynamic changes of tumor necrosis factor (TNF)- α and interleukin (IL)-1 β levels in aqueous humor (AH) of the second eye and whole blood after the first eye cataract surgery. A rabbit model of monocular phacoemulsification was established by administration of 0.3% levofloxacin. Whole blood and AH samples from non-surgical eyes in the experimental group (n =25) and second eye in the blank control group (n =15) were obtained and corneal sensitivity was examined after surgery (1, 3, 7, 14, and 21 days postoperatively). TNF- α and IL-1 β levels in AH and TNF- α mRNA and IL-1 β mRNA levels in whole blood were measured. In a clinical study, 30 patients who underwent bilateral phacoemulsification within 1 month were divided into six groups in accordance with the operation intervals (1, 3, 7, 10, 14, and 21days). TNF- α and IL-1 β levels in AH were measured at the beginning of surgery and intraoperative pain was assessed immediately after surgery. Corneal sensitivity (F =244.910, P <0.05), TNF- α and IL-1 β levels in AH (F =184.200, 82.900, P <0.05) of non-surgical eyes and in whole blood (F =272.800, 193.530, P <0.05) in the experimental group were significantly higher than the baseline levels after phacoemulsification. In the clinical study, NRS scores of second eye surgery were higher than those of the first eye(P =0.0025) and 19 (63.3%) patients reported more pain during the second eye surgery. TNF- α and IL-1 β concentrations in AH of the second eye were significantly higher than those of the first eye (F =123.60, P <0.05; F =59.60, P <0.05). In conclusion, within 1 month after the first eye phacoemulsification, higher pain sensitivity (hyperalgesia) exists in the second eye, which may be related to dynamic changes in TNF- α, IL-1 β levels in AH or whole blood.